PARENTS OF CHILDREN WITH LEARNING DISABILITIES: FACTORS PREVENTING PARENTS FROM GETTING LEARNING SUPPORT - Ahmad, Mohd.Sharani (Southeast Asia Early Childhood Journal, 2015)
A case study design was chosen in order to explore answers to the question of, what factors prevent parents from getting learning support for their children in the pre school class? The purpose of using a case study was to gain an understanding of the research question from the participants’ perspective. The case study was made up of sub-cases that were parents of children who all went to a particular pre school at the time of their referral for assessment of learning disabilities. The data collected through unstructured interviews were analysed using the constant comparative method. The finding that emerged as a major factor that prevented parents from getting learning support when children started failing in the basic scholastic skills of reading, spelling and mathematics. The other factors that were identified related to parents’ understanding of their children’s learning disabilities; their being illiterate; and the belief in cultural issues. Recommendations were suggested for both the pre school teacher and helpers relating to the need for parent education on the learning and development of their children with specific emphasis on learning disabilities. The role parents can play to develop in getting learning support with educators was also highlighted.